Navigating the Deep Approach to Learning in Islamic Education: A Study of Its Implementation at State Senior High School - Delsia Pebrianti; Sulistyowati Sulistyowati; Nurul Hikmah (STAI Syaichona Moh. Cholil Bangkalan, 2026)
This study employed a qualitative descriptive design to analyze the implementation of the Deep Approach to Learning in Islamic Education at State Senior High School 1 Palangka Raya under the Merdeka Curriculum. Data were collected through classroom observations, in-depth interviews, and document analysis involving Islamic Education teachers, the principal, the Vice Principal of Academic Affairs, and Grade 10 students. The findings reveal that the Deep Approach to Learning was implemented through three stages: planning, instructional implementation, and evaluation, which emphasize meaningful, mindful, and joyful learning principles. This study contributes novel insights by demonstrating that the Deep Approach to Learning not only enhances students’ conceptual understanding but also strengthens the internalization of religious values through reflective activities, socially contextualized projects, and spiritual integration in classroom practices. Furthermore, the study identifies institutional support and teacher readiness as critical success factors, while uneven student participation and limited conceptual understanding among teachers remain key challenges. These findings extend existing literature by highlighting the pedagogical, spiritual, and character dimensions of the Deep Approach to Learning in Islamic Education.